Solution formulation development and efficacy of MJC13 in a preclinical model of castration-resistant prostate cancer. (2nd January 2016) - Liang, Su; Bian, Xiaomei; Liang, Dong; Sivils, Jeffrey C.; Neckers, Leonard M.; Cox, Marc B.; Xie, Huan
Abstract: MJC13, a novel FKBP52 targeting agent, has potential use for the treatment of castration-resistant prostate cancer. The purpose of this work was to develop a solution formulation of MJC13, and obtain its efficacy profile in a human prostate cancer xenograft mouse model. Preformulation studies were conducted to evaluate the physicochemical properties. Co-solvent systems were evaluated for aqueous solubility and tolerance. A human prostate cancer xenograft mouse model was established by growing 22Rv1 prostate cancer cells in C.B-17 SCID mice. The optimal formulation was used to study the efficacy of MJC13 in this preclinical model of castrate-resistant prostate cancer. We found that MJC13 was stable (at least for 1 month), highly lipophilic (logP = 6.49), poorly soluble in water (0.28 µg/mL), and highly plasma protein bound (>98%). The optimal formulation consisting of PEG 400 and Tween 80 (1:1, v/v) allowed us to achieve a MJC13 concentration of 7.5 mg/mL, and tolerated an aqueous environment. After twice weekly intratumoral injection with 10 mg/kg MJC13 in this formulation for four consecutive weeks, tumor volumes were significantly reduced compared to vehicle-treated controls.